Naat of the Prophet ﷺ in the poetry of Saadi Shirazi - Hayat, Shaukat; Rehman, Naseem ur (sourcecoder, 2024)
Devotion and love to the Prophet of Allah Hazrat Muhammadﷺ is a characteristic of every Muslim. Without love and devotion to the Messenger ﷺ, there is no fulfillment of faith. Naat, like other genres of poetry, first originated in the Arabic language. Naat in Persian started under the influence of Arabic language.Famous Persian poets like Abul Qasim Ferdowsi, Abu Saeed Abul Khair, Khaqani Shirwani, Hakeem Sanai Ghaznavi, Fariduddin Attar, Nizami Ganjavi, Maulana Jalaluddin Rumi, Saadi Shirazi, Amir Khusro, Urfi Shirazi, Abdul Rahman Jami and Qudsi Mashdi etc have specially included the subject of naat in their poetry.As the Persian language began to develop and the poetry began to be written in it, from that time, along with the other genres of poetry such as ghazal, masnavi, qasida, rubai etc, Naat has also been an important part of the Persian poetry. Thus began the endless series of Naatia Poetry in Persian which continues till now. Saadi Shirazi, who is a well-known Persian poet and also holds a prominent position in Sufism and mysticism, has also written very beautiful poems in the field of Naat. In this paper, Natia poetry of Saadi Shirazi will be described.